Ultrasonic velocity and acoustic emission properties of concrete eroded by sulfate and its damage mechanism - LIU Juan-hong; ZHAO Li; SONG Shao-min; JI Hong-guang (工程科学学报)
Simulation experiment was performed on the performance of concrete exposed to sulfate attack and dry-wet cycles. Changes in ultrasonic velocity and acoustic emission activities for concrete at different erosion periods were tested by uniaxial compression test. The damage mechanism was analyzed by environmental scanning electron microscopy (ESEM), energy-dispersive X-ray analysis (EDX) and X-ray diffraction (XRD). The results show that at the beginning of loading for concrete after 60 d and 80 d erosion, the specimen exhibits a significant compaction phase. The longer the concrete is exposed to sulfate attack and dry-wet cycles, the earlier the sudden drop in ultrasonic velocity occurs. For concrete after 40 d erosion, the active zone of acoustic emission is narrow during the loading process. The problems of stress concentration and a sudden release of energy tend to occur at the weak position caused by erosion in concrete, and a sharp increase in acoustic emission events appears in advance under sulfate attack. By means of a mathematical model, the damage model of concrete was established based on the cumulative ring-down count of acoustic emission as a variable, which reveals the relations of sulfate attack, load and damage for concrete in complex underground environments. During erosion time, the expansions caused by ettringite and gypsum and the swelling of sodium sulfate crystallization result in the evolution of micro-destruction, leading to the different macroscopic properties of corroded concrete.